2019
DOI: 10.1002/hbm.24859
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced striatal and prefrontal activity is associated with individual differences in nonreinforced preference change for faces

Abstract: Developing effective preference modification paradigms is crucial to improve the quality of life in a wide range of behaviors. The cue-approach training (CAT) paradigm has been introduced as an effective tool to modify preferences lasting months, without external reinforcements, using the mere association of images with a cue and a speeded button response. In the current work for the first time, we used fMRI with faces as stimuli in the CAT paradigm, focusing on face-selective brain regions. We found a behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(52 citation statements)
references
References 68 publications
9
43
0
Order By: Relevance
“…Our results are in line with previous reports of choice-induced preference changes (Ariely & Norton, 2008;Brehm, 1956;Izuma et al, 2010;Sharot et al, 2010) and conceptually replicate studies showing changes in stimulus valuation by cued approach training (CAT) (Aridan, Pelletier, Fellows, & Schonberg, 2019;Botvinik-Nezer, Bakkour, Salomon, Shohamy, & Schonberg, 2019;Salomon, Botvinik-Nezer, Oren, & Schonberg, 2019;Schonberg et al, 2014). Similar to the present approach, performance of a button press ("go" response) upon presentation of "go" stimuli during CAT reliably induces long-term nonreinforced changes of desirability and choice probabilities of "go" stimuli over "no-go" stimuli.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in line with previous reports of choice-induced preference changes (Ariely & Norton, 2008;Brehm, 1956;Izuma et al, 2010;Sharot et al, 2010) and conceptually replicate studies showing changes in stimulus valuation by cued approach training (CAT) (Aridan, Pelletier, Fellows, & Schonberg, 2019;Botvinik-Nezer, Bakkour, Salomon, Shohamy, & Schonberg, 2019;Salomon, Botvinik-Nezer, Oren, & Schonberg, 2019;Schonberg et al, 2014). Similar to the present approach, performance of a button press ("go" response) upon presentation of "go" stimuli during CAT reliably induces long-term nonreinforced changes of desirability and choice probabilities of "go" stimuli over "no-go" stimuli.…”
Section: Discussionsupporting
confidence: 93%
“…configural) object representations that this region supports. This is compatible with previous findings that the change in value of faces and objects is associated with changes in face and object processing regions, respectively (Botvinik-Nezer et al, 2020; Salomon et al, 2020), arguing that value learning and storage occurs partly through experience-dependent plasticity in sensory cortex (Schonberg and Katz, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…The pre-registered model did not include accuracy confound regressors (one for value modulation during object presentation and one for value-modulation during value rating), which we added after behavioural data analysis revealed a trend difference in accuracy between conditions. We also controlled for reaction times differently than what was stated in the pre-registration, this was done due to a mistake in the pre-registered analysis plan that was different from the usual process of accounting for RT (Botvinik-Nezer, Salomon, and Schonberg 2020; Salomon et al 2020; Schonberg et al 2014). These changes to the GLM make the model more stringent and allow for a clearer interpretation of the value-related activations reported here, ruling out the possibility that they might reflect reaction-time or difficulty/accuracy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, although the effect of CAT on choices has been shown repeatedly (e.g., Bakkour et al, 2016;Schonberg et al, 2014;, to date only a few experiments examined whether CAT increases visual attention for cued over uncued items (Salomon et al, 2019;Schonberg et al, 2014), and only one experiment showed this effect (Schonberg et al, 2014). Thus, it could also be that this initially reported effect of CAT on visual attention is not so robust as the behavioural effect.…”
Section: Discussionmentioning
confidence: 96%